Current state and prospects for the development of digitalization of industrial enterprises in Ukraine - Pererva, P. G.; Nesterov, Dmytro (OKTAN PRINT, 2025)
The article examines the current state and future prospects of digitalization in industrial enterprises in Ukraine. It highlights the structural and technological challenges that hinder the effective implementation of digital tools, including outdated infrastructure, insufficient investment, and regulatory barriers. At the same time, the study emphasizes the opportunities associated with Industry 4.0, integration into global value chains, and the adoption of advanced digital platforms for production management. The findings suggest that successful digital transformation requires coordinated efforts between enterprises, government institutions, and international partners to ensure competitiveness and sustainable growth in the Ukrainian industrial sector.
Keywords: digitalization; industrial enterprises; Ukraine; Industry 4.0; competitiveness; innovation; sustainable development; technological transformation